PREDICTION OF BUCKLING OF RHS COLUMNS USING FINITE ELEMENT ANALYSIS METHOD - SIVAN, SAILENDRA (Universiti Teknologi PETRONAS, 2021)
In a structural system, column is a vertical structural member whose longitudinal dimension exceeds the lateral dimension of the section. The column failure modes include short column compression failure and long column buckling failure. In the overall design process mechanics, column buckling is a special and inquisitive emphasis with which the loss is not attributed to the material strength. As in the factory plants and process facilities, it is a common practice to use RHS Columns as structural elements, however the behavioral changes on buckling of RHS Columns as consequence of combination of variations parameters such the boundary conditions, wall thickness, columns lengths and especially on structural openings in the cut-out configuration, shape, size, location and numbers are not well understood. Thus, in this project, parametric study was conducted to predict the buckling of RHS Columns with varying parameters using Finite Elements Analysis and the finding are compared results obtained using the proposed approach in Eurocode 3.